Internetworking with TCP/IP - Comer, Douglas (Prentice-Hall, 1995)
The third edition of this all-time best-selling book is still the reference for anyone who wants to work with the TCP/IP protocol suite. TCP/IP and ATM are two of the most important networking technologies. This is the first book that shows how to use the two technologies together.